ANALYSIS OF SOFT GROUND REINFORCED BY NON-HOMOGENEOUS GRANULAR PILE-MAT SYSTEM - Jagdish T. Shahu; Shigenori Hayashi; Madhira R. Madhav (Lowland Technology International, 2000)
Due to differences in compaction characteristics and overburden stresses, modulus of the deformation of granular piles shows variation with depth and granular piles may be considered as non-homogeneous. A simple theoretical approach to analyze soft ground reinforced by non-homogeneous granular piles with granular mat on top is represented. The proposed model is validated by comparison with other numerical models and field test results. A non-homogeneous grnular pile is found to be more beneficial than the homogeneous one. For the case of non-homogeneous granular piles, due to increase in granular pile modulus with depth, shear stresses between the granular pile and the surrounding soft soil and the total settlement reduce by a significant amount. The variation of stress concentration factor with depth tends to become more uniform as the rate of variation of granular pile stiffness with depth increases. The reduction in shear stresses due to non-homogeneity of granular pile is found to be very high at low values or area ratio. This is highly desirable for stabilization of soft soils having low shear strength.